THE EFFECTIVENESS OF PROBLEM-BASED LEARNING ON THE DEVELOPMENT OF SPATIAL SKILLS AMONG JUNIOR HIGH SCHOOL STUDENTS: A SYSTEMATIC LITERATURE REVIEW: Jawa Timur, Indonesia - Idzni Arenta Dinia Putty; Fatqurhohman; Nurul Imamah Ah (Universitas Muhammadiyah Bengkulu, 2025)
Many reports show that Junior High School students still face difficulties in spatial abilities, especially in geometry. Students often struggle with visualizing objects, interpreting 3D representations, and performing mental rotations. Learning that is still teacher-centered also limits students’ opportunities to explore and develop spatial reasoning. This study aims to analyze the effectiveness of the Problem Based Learning (PBL) model in developing students’ spatial abilities through a systematic literature review (SLR) approach. The review was conducted using the PRISMA guidelines to ensure a transparent and comprehensive selection process. The study examined eight selected articles identified by Google Scholar, Garuda, and Academia. The analysis reveals that PBL effectively enhances middle school students’ spatial abilities in mathematics, particularly in visualization, mental rotation, and spatial reasoning. The model also strengthens critical, creative, and reflective thinking as essential 21st-century competencies. Furthermore, technology-assisted PBL such as SketchUp and differentiated facilitation based on cognitive styles further optimize learning outcomes. However, challenges remain in teacher readiness and access to digital media. The findings confirm that PBL is not only an effective instructional method but also a transformative pedagogical approach to cultivate spatial intelligence and problem-solving skills in mathematics education. Keywords: Problem Based Learning, Spatial Ability, Mathematics Education, 21st-Century Skills, Systematic Literature Review